Systemic change processes: a framework for exploring weight loss and weight loss maintenance processes within the individual and family context - Macchi, C.R. (Kansas State University, 2006)
Despite multiple interventions and the increase of consumer spending on weight management, weight loss maintenance continues to allude most people. This study explores women’s narratives and the ways they made meaning of their weight loss and weight loss maintenance experiences. Examining the processes occurring within the individual and the family context, this study investigated the potential differences between weight loss and weight loss maintenance processes. A grounded theory approach guided the study design, transcription coding, and data analysis. The results revealed four categories (cycles and patterns, fluctuations and thresholds, defining self, and contextual connections) emerging from the research participants’ narratives describing their weight loss and weight loss maintenance experiences. An analytical framework, consisting of the examination of clustered categories using a multifocal lens and a toggling procedure, facilitated the development of multidimensional descriptions of the women’s experiences and guided the process of analysis. The process of analysis was isomorphic to the process the women used to formulate their narratives. The women incorporated multiple dimensions of their experiences to create narratives that described and informed their weight loss and weight loss maintenance efforts. The analysis also revealed that weight loss and weight loss maintenance are multi-dimensional processes. The dimensions reflect both similarities and differences between the processes. Some women used heroic while others used integrative efforts to lose weight. Their efforts impacted the amount of overlap they experienced between the weight loss and weight loss maintenance processes. Implications for further studies are presented for using the analytical framework to understand the meaning-making processes occurring with weight loss and weight loss maintenance. Potential clinical implications for addressing weight loss and weight loss maintenance within family and relational contexts are explained.
Keywords: Weight loss; Weight loss maintenance; Family therapy; Qualitative research; Systemic change processes; Narrative; Health Sciences, General (0566); Psychology, Behavioral (0384); Psychology, Social (0451)